A ship domain-based model of collision risk for near-miss detection and Collision Alert Systems. (October 2021) - Szlapczynski, Rafal; Szlapczynska, Joanna
Highlights: decomposes ships encounter into phases based on ship arena and domain violations. takes into account the impact of late manoeuvres and surrounding traffic. introduces new encounter-related decision variables. aggregates decision variables into Collision Risk Index by decision rules. outlines possible applications to near-miss detection and Collision Alert System. Abstract: The paper presents a new model of ship collision risk, which utilises a ship domain concept and the related domain-based collision risk parameters. An encounter is here described by five variables representing: degree of domain violation (DDV), relative speed of the two vessels, combination of the vessels' courses, arena violations and encounter complexity. As for the first three variables, their values can be directly computed based on positions, courses and speeds of two vessels. The last two variables require decomposing a close quarters situation into phases. For this purpose the method utilizes a number of auxiliary parameters derived from the concept of ship domain: time of domain violation (TDV), time of domain exit (TDE), timespan of close quarters situation and vessels' proximity, which is quantified based on the ship arena. The formulas and algorithms for determining all variables' values are provided in detail. Once all the values are computed, the final collision risk assessment is made. Possible applications of the presented model include: AIS-based near-miss detection, Collision Alert Systems (CAS) and collision avoidance decision support systems (DSS). Case studies for those applications are provided, including examples of encounter classification and quantification of collision risk.